2005
DOI: 10.1007/s00280-005-1005-4
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant inhibits cyclophosphamide bioactivation and thiotepa metabolism

Abstract: Aprepitant inhibited both cyclophosphamide and thiotepa metabolism, most probably due to inhibition of the CYP 3A4 and/or 2B6 isoenzymes. The effects of this interaction are, however, small compared to the total variability. Addition of aprepitant may provide superior protection against vomiting in patients receiving the highly emetogenic high-dose CTC chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Phosphoramide mustard and acrolein are two active CP metabolites produced by liver microsomal enzymes (De Jonge et al, 2005). CP's antineoplastic effects are associated with phosphoramide mustard, while acrolein is linked with its toxic side effects (Kern & Kehrer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoramide mustard and acrolein are two active CP metabolites produced by liver microsomal enzymes (De Jonge et al, 2005). CP's antineoplastic effects are associated with phosphoramide mustard, while acrolein is linked with its toxic side effects (Kern & Kehrer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Competition with 4-hydroxylation is the major oxidative pathway that causes the dechloroethylation and the formation of the neurotoxic metabolites chloroacetaldehyde and 2-and3-dechloroethylifosfamide. The potential inhibition of CYP3A4 by aprepitant [18] may increase the levels of ifosfamide metabolites resulting in accumulation and further risk of encephalopathy and other side effects like hemorrhagic cystitis or neutropenia [14].…”
Section: Discussionmentioning
confidence: 99%
“…3 de Jonge et al 4 have shown that aprepitant inhibits cyclophosphamide metabolism, thus resulting in decreased formation of 4-HOCP.…”
mentioning
confidence: 99%
“…3 The alkylating agent cyclophosphamide is an inactive prodrug that requires activation to form its active metabolite 4-hydroxycyclophosphamide (4-HOCP), with major participation by CYP2A6, CYP2B6 and CYP3A4. 3 de Jonge et al 4 have shown that aprepitant inhibits cyclophosphamide metabolism, thus resulting in decreased formation of 4-HOCP.…”
mentioning
confidence: 99%
See 1 more Smart Citation